2005
DOI: 10.1016/j.scitotenv.2004.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Particle and carbon dioxide emissions from passenger vehicles operating on unleaded petrol and LPG fuel

Abstract: A comprehensive study of the particle and carbon dioxide emissions from a fleet of six dedicated liquefied petroleum gas (LPG) powered and five unleaded petrol (ULP) powered new Ford Falcon Forte passenger vehicles was carried out on a chassis dynamometer at four different vehicle speeds--0 (idle), 40, 60, 80 and 100 km h(-1). Emission factors and their relative values between the two fuel types together with a statistical significance for any difference were estimated for each parameter. In general, LPG was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 14 publications
5
46
0
2
Order By: Relevance
“…LPG is regarded as cleaner fuel than diesel or gasoline, emitting less greenhouse gases, particulate matters, ozone precursors, and polycyclic aromatic hydrocarbons (Chang et al, 2001;Ristovski et al, 2005;Lim et al, 2007;Yang et al, 2007;Adam et al, 2011), and is currently widely used in buses and taxies in China (Ou et al, 2010). About 5000 buses and 9300 taxies in Guangzhou were LPG-powered in 2005 and the numbers increased to 6430 and 16000 in 2006, respectively.…”
Section: Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…LPG is regarded as cleaner fuel than diesel or gasoline, emitting less greenhouse gases, particulate matters, ozone precursors, and polycyclic aromatic hydrocarbons (Chang et al, 2001;Ristovski et al, 2005;Lim et al, 2007;Yang et al, 2007;Adam et al, 2011), and is currently widely used in buses and taxies in China (Ou et al, 2010). About 5000 buses and 9300 taxies in Guangzhou were LPG-powered in 2005 and the numbers increased to 6430 and 16000 in 2006, respectively.…”
Section: Calculationmentioning
confidence: 99%
“…About 5000 buses and 9300 taxies in Guangzhou were LPG-powered in 2005 and the numbers increased to 6430 and 16000 in 2006, respectively. However, some on-road studies demonstrated that differences between LPG-and gasoline-vehicle emissions were not statistically significant owing to the large variations between vehicles (Ristovski et al, 2005), e.g., intensive use and poor maintenance of LPG-vehicles resulted in exceedances of emission standards (Ning and Chan, 2007;Lau et al, 2011). Unmatched engines and incomplete combustion of LPG could also offset its potential benefits (Lai et al, 2009;Adam et al, 2011).…”
Section: Calculationmentioning
confidence: 99%
“…State-of-the-art GDI engines combined with boosting technology offer higher specific power, lower fuel consumption and faster response than conventional port fuel injection (PFI) engines [3][4][5][6][7]. In spite of these many advanced technologies, many studies have indicated that the mixture preparation schemes and combustion mechanisms of the GDI engine emit significantly higher amounts of particulate matter (PM) than the traditional PFI engines or diesel engines that have been equipped with particulate filters, especially during the cold-start phase and at high acceleration points [5,6,[8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…O balanço ideal entre ar e combustível é atingido quando a percentagem de dióxido de carbono é maximizada, reduzindo a emissão de outros componentes nocivos, como monóxido de carbono, hidrocarbonetos e óxidos de nitrogênio. [12,3] • Vazamentos em tubulações Em plantas industriais onde a utilização de CO 2 passa por tubulações, pode ser de interesse instalar detectores em juntas e conexões ou locais mais propícios a vazamentos. A detecção de um problema pode ser informada a um sistema automático de alarme capaz de prevenir acidentes mais graves.…”
Section: Considerações Finais a Aplicações Práticasunclassified
“…Além do emprego em aplicações ambientais, este tipo de sistema pode ser utilizado para monitorar vazamentos de gás em tubulações, medição da emissão veicular por motores à combustão, diagnóstico médico de doenças respiratórias, dentre outras aplicações em diversas áreas [2,3].…”
Section: Introductionunclassified